Human–animal contact to inform zoonotic disease risk across gradients of agricultural land use change in the Central River Region (CRR) of The Gambia (ZooContact): a formative study - Ahmed, Aliyu N.; Fornace, Kimberly; Iwamura, Takuya; Murray, Kris A. (Frontiers in Public Health, 2024)
biodiversity assessment. For survey effort, one field assistant interviewed 25 participants per week. It took a total of one (1) hour to complete an interview including random household selection, consenting, and questionnaire interview.The pilot study confirmed the feasibility of the research and informed the design of the larger study. Key parameters, such as community access, acceptability, recruitment success, and logistical requirements, allowed for robust sample size calculations and realistic project cost estimates. Additionally, the study enabled the research team to familiarize themselves with the communities and refine the full study methods